Analisis Ekonomis, Efisiensi dan Efektivitas Anggaran Pendapatan dan Belanja - Sumartin Selfina Lona; M. E. Perseveranda; Henny A. Manafe (Politeknik Ganesha Medan, 2023)
The objective of this study was to understand the economical, efficient and effective implementation of the State Revenue and Expenditure Budget at the government institution. Data sources used in this study are financial reports especially budget ceiling and budget realization between the period of 2017 and 2021 fiscal year was obtained from The Online Monitoring of the State Accounting Treasury System, the Ministry of Finance of the Republic of Indonesia. The descriptive and comparative analyses were employed in this study. The results of the research show that Economic level in 2017-2021 fiscal year utilisation felt into the economical category as shown by the percentage of budget realization was less than 100% (<100%). The effective level of achievement for non-tax state income realisation between 2017 and 2021 fiscal year felt into a very effective criteria with the effective ratio was 103.62%; while that for the expenditure felt into a sufficient effective criteria with an average effective ratio was 91.30%. Cost efficiency ratio/expenditure realization to achieve the maximum revenue in the period of 2017 – 2021 suits for a very efficient category with the ratio for each fiscal year was less than 19%; thus economical, efficient and effective implementation of State Revenue and Expenditure Budget must continue to be improved